Good Corporate Governance Characteristic, Profitability and Firm Value: Evidence from Indonesia - Dwi Susilowati; Nurlia Nurlia; Juwari Juwari (Fakultas Ekonomi, UIN Maliki Malang, 2022)
This research aims to test the influence of good corporate governance (independent commissioners, institutional ownership, board of directors, and audit committees) and profitability on the firm value. This research was conducted because of the low GCG implementation in Indonesia. This study used multiple linear regression to test the influence between variables and Sobel tests to determine the mediation effect of profitability. The research was conducted on companies registered in LQ45 for the years 2015-2019. The data used in the study was 245 data. The results showed that independent commissioners and audit committees had a negative effect, the board of directors had a positive effect, and institutional ownership did not affect profitability. Direct testing of GCG's influence on the firm values showed that independent commissioners had a negative effect, institutional ownership had a positive effect, and the board of directors and audit committee did not affect the firm value. The results also showed that profitability could mediate the influence of GCG on the firm value except for institutional ownership variables. Further research is expected to increase the number of samples and use different measurements of the firm. Companies need to improve GCG to increase management transparency so that investors and creditors can make appropriate decisions about the company.